Use of Independent and Clitic Forms of Non-Reﬂexive Personal Pronouns in Sixteenth-Century Standard Slovenian - Jelovšek, Alenka (Jezikoslovni zapiski, 2018)
This article presents the use of independent and clitic forms of non-reﬂexive personal pronouns in sixteenth-century standard Slovenian. It presents phrases in which the use of one or the other was fxed, and other examples highlighting the diﬀerences between individual authors and, within their works, also between individual pronouns and clitics. In addition, the situation in Old Church Slavic and in older preserved Slovenian manuscripts is comparatively described. The conclusion evaluates possible explanations for such use in the sixteenth century.